Glycans pave the way for immunotherapy in triple-negative breast cancer - Girotti, Maria Romina (2018)
The clinical efficacy of therapies targeting the PD-1/PD-L1 pathway is still limited. In this issue of Cancer Cell, Li and colleagues identify a PD-L1 glycosylation-based mechanism in triple-negative breast cancer that fosters immunosuppression by enhancing interactions with PD-1. Targeting glycosylated PD-L1 with a drug-conjugated antibody opens new avenues for treatment. The clinical efficacy of therapies targeting the PD-1/PD-L1 pathway is still limited. In this issue of Cancer Cell, Li and colleagues identify a PD-L1 glycosylation-based mechanism in triple-negative breast cancer that fosters immunosuppression by enhancing interactions with PD-1. Targeting glycosylated PD-L1 with a drug-conjugated antibody opens new avenues for treatment.